Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{5}{6}\times3+\dfrac{20}{6}\times2-1:\dfrac{6}{5}\)
\(=\dfrac{5}{6}\times3-\dfrac{5}{6}+\dfrac{20}{6}\times2\)
\(=\dfrac{5}{6}\times\left(3-1\right)+\dfrac{20}{6}\times2\)
\(=\dfrac{5}{6}\times2+\dfrac{20}{6}\times2\)
\(=\left(\dfrac{5}{6}+\dfrac{20}{6}\right)\times2\)
\(=\dfrac{25}{6}\times2\)
\(=\dfrac{25}{3}\)
#DatNe
\(\dfrac{5}{6}\) \(\times\) 3 + \(\dfrac{20}{6}\) \(\times\) 2 - 1 : \(\dfrac{6}{5}\)
= \(\dfrac{5}{6}\) \(\times\) 3 + \(\dfrac{20}{6}\) \(\times\) 2 - \(\dfrac{5}{6}\)
= \(\dfrac{5}{6}\) \(\times\) 3 + \(\dfrac{5}{6}\) \(\times\) 8 - \(\dfrac{5}{6}\) \(\times\)1
= \(\dfrac{5}{6}\) \(\times\) ( 3 + 8 - 1)
= \(\dfrac{5}{6}\) \(\times\)10
= \(\dfrac{25}{3}\)
1: Sửa đề: 3x-5
\(=\dfrac{-x^2\left(3x-5\right)-3\left(3x-5\right)}{3x-5}=-x^2-3\)
2: \(=\dfrac{5x^4-5x^3+14x^3-14x^2+12x^2-12x+8x-8}{x-1}\)
=5x^2+14x^2+12x+8
3: \(=\dfrac{5x^3+10x^2+4x^2+8x+4x+8}{x+2}=5x^2+4x+4\)
4: \(=\dfrac{\left(x^2-1\right)\left(x^2+1\right)-2x\left(x^2-1\right)}{x^2-1}=x^2+1-2x\)
5: \(=\dfrac{x^2\left(5-3x\right)+3\left(5-3x\right)}{5-3x}=x^2+3\)
a: \(P\left(x\right)=6x^3+4x^2+2x-4\)
\(Q\left(x\right)=-x^4+6x^3-4x^2+3x-8\)
b: \(P\left(x\right)-Q\left(x\right)=x^4+8x^2-x+4\)
\(P\left(x\right)+Q\left(x\right)=-x^4+12x^3+5x-12\)
4/6x1/5+4/6x3/5+2/6x4/5
=4/6.(1/5+3/5)+2/6.4/5
=4/6.4/5+2/6.4/5
=4/5.(4/6+2/6)
=4/5.6/6
=4/5.1 = 4/5
\(a,N\left(x\right)=x^2+3x^4-2x-x^2+2x^3=3x^4+2x^3+\left(x^2-x^2\right)-2x\\ =3x^4+2x^3-2x\\ P\left(x\right)=-8+5x-6x^3-4x+6=-6x^3+\left(5x-4x\right)+\left(-8+6\right)\\ =-6x^3+x-2\)
Bậc của N(x) là 4
Bậc của P(x) là 3
\(b,P\left(x\right)+N\left(x\right)=3x^4+2x^3-2x-6x^3+x-2\\ =3x^4+\left(2x^3-6x^3\right)+\left(-2x+x\right)-2\\ =3x^4-4x^3-x-2\)
\(c,B\left(x\right)=-2x^2\left(x^3-2x+5x^2-1\right)\\ =\left(-2x^2\right).x^3+\left(-2x^2\right).\left(-2x\right)+\left(-2x^2\right).5x^2+\left(-2x^2\right).\left(-1\right)\\ =-2x^5+4x^3-10x^4+2x^2\\ =-2x^5-10x^4+4x^3+2x^2\)
Trl:
3 x 9 + 6 x 3 + 5 : 2 - 6 + 9 x 3 - 2
= 27 + 18 + 2,5 - 6 + 27 - 2
= 66,5
#HuyềnAnh#
Trl :
3 x 9 + 6 x 3 + 5 : 2 - 6 + 9 x 3 - 2
= 27 + 18 + 2,5 - 6 + 27 - 2
= 45 + 2,5 - 6 + 27 - 2
= 66,5
_ Jie _
Trả lời :
108 x 6 + 68 = 716
248 : 6 : 2 = 62/3
269 x 5 - 3 =1342
150 : 6 x 3 =75
5+6x3-8+6-2
=5+18-8+6-2
=23-8+6-2
=15+6-2
=21-2
=19
= 19 nha em